Simulating breast cancer position in body with heat changes using thermal texture mapping (TTM) - 509242 Normazida Ab. Lah; Manan Munhamad Jaib (2007)
Project Paper (Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2007